Costs in value-based health care dashboards: a qualitative study on stakeholder requirements - Esmée K. J. van der Poort; Danny van der Helm; Aiko P. J. de Vries; Wilbert B. van den Hout; M. Elske van den Akker-van Marle (BMC Health Services Research)
Abstract Background An essential element of Value-Based Health Care (VBHC) is the use of population dashboards to evaluate and monitor the improvement of the value of care delivery in integrated practice units (i.e. care pathways). VBHC defines value as patient-relevant outcomes relative to costs, but in practice, costs are often overlooked. Therefore, this study aimed to explore functional, operational, and technical requirements for the implementation of costs in VBHC dashboards. Methods A qualitative study was performed at the organ transplant center of Leiden University Medical Center in the Netherlands. Qualitative data were collected using 15 semi-structured interviews, with stakeholders from four different categories: (1) health care providers, (2) management, (3) finance and IT, and (4) patients. Transcripts were analyzed using thematic analysis and deductive coding based on requirements analysis. Results This study identified three functional requirements for the implementation of costs in VBHC dashboards. All stakeholder groups aimed to (1) identify costs and resources and (2) evaluate the value of care, whereas management additionally saw a role in (3) monitoring the financial viability of a care pathway. The required cost indicators could be categorized into four categories: cost of care activities, resources used to deliver care, income (e.g., reimbursements), and patient costs (e.g., out-of-pocket). In terms of operational requirements, costs should be reviewed monthly to quarterly in a recurring meeting, collectively by the care team and a financial expert. Technical requirements were a costing model that accurately captures all costs in care delivery, is validated, and provides up-to-date estimates. In addition, the dashboard interface should be embedded in existing IT systems to increase usability. Conclusions This study supports the implementation of costs in VBHC dashboards through actionable requirements. By understanding key functional, operational, and technical requirements from different stakeholder perspectives, hospital cost data can be effectively integrated to improve the value of care delivery and monitor the financial viability of care pathways. Future research should focus on the role of patient-relevant costs in the data-driven improvement of VBHC delivery.